The preparation of complementary food for breastmilk after the earthquake in Malampah, Pasaman Districts, West Sumatra Province in 2022 - Lestari Dya Mulya; Masnadi Nice Rachmawati (E3S Web of Conferences)
A seismic event of 6.2 magnitude occurred on February 25, 2022, causing significant earthquake in West Pasaman Regency and Pasaman Regency. It is evident that children under the age of five constitute the second biggest group of refugees Toddlers who do not get fed properly and are in an environment with poor sanitation can be threatened by various diseases. Implementing regular supplemental feeding techniques in catastrophe settings is a crucial strategy for improving children’s nutritional condition. This paper is based on several literature studies that refer to several literatures. Access to facilities and infrastructure influences disaster food assistance. Public kitchens were quickly created in West Pasaman, especially Pasaman District, after the earthquake. Lack of potable water and four-wheeled vehicle access restricted camp food production. Food from PERSAGI and contributors is distributed in Puskesmas Ladang Panjang Malampah. Even in emergencies, typical supplementary meals can be provided. In disasters, primary carers or parents require help governing complementary food provision based on clean water, convenient cooking facilities, diversified food items, or home-cooked, local-culture complementary meals. In addition to facility support, health workers must teach parents about standardised supplementary meals and give them confidence to offer them in emergencies